Bridging the gap: the impact of parental education and child leisure activities on cognitive and socioemotional skills in preschoolers - Shatskaya, Arina; Tarasova, Kristina; Surilova, Irina (Frontiers in Psychology, 2025)
Family socioeconomic status is broadly acknowledged to be associated with child development and wellbeing. However, the extent of this association across various dimensions of child development remains a topic of ongoing debate. This study aims to investigate the relationship between parental education and child cognitive and socioemotional skills, as well as the mediating role of children's leisure time activities, including screen time and shared book reading. The study involved 1,288 preschool children (M = 70.4 months, SD = 4.53) and their parents. Children's executive functions, emotion comprehension, and peer acceptance were assessed. Parents provided information regarding their educational levels; their children screen time duration and frequency of shared book reading. The conducted assessment of direct and indirect effects through path analysis revealed following findings. First, parental education is related to children's verbal working memory, cognitive flexibility, and emotional comprehension. Second, it showed no significant relation to children's peer acceptance, visual working memory, or inhibitory control. Third, shared book reading and screen time can statistically significantly explain differences in verbal working memory between children, including those associated with differences in parental education. Therefore, low reading frequency and high screen time, often observed in families with lower parental educational attainment, may serve as potential sources of disparities in children achievement and psychological wellbeing throughout development.